Driving Performance in Islamic Banking: How Discipline, Compensation, and Education Intersect - Kapita Tantri (CV. Era Digital Nusantara, 2025)
The purpose of this study is to examine the role of discipline, work compensation, and educational background in enhancing employee performance at Bank Syariah Indonesia KC Sudirman Palembang. The population consists of all employees, with a saturated sampling technique applied so that the entire population of 47 respondents was included. Primary data were collected through questionnaires and analyzed using SmartPLS, covering measurement models (outer model), structural models (inner model), and hypothesis testing. The findings reveal that discipline, work compensation, and educational background contribute positively and significantly to employee performance. The novelty of this research lies in the simultaneous integration of these three key human resource management factors within the context of Islamic banking, which has rarely been investigated. Practically, the results provide valuable insights for Islamic bank management in designing policies that strengthen workplace discipline, establish fair compensation systems, and align career development strategies with employees’ educational backgrounds. Thus, this study not only reinforces human resource management theory in Islamic banking but also offers actionable recommendations to improve productivity and service quality in Indonesia’s Islamic financial institutions.